To which genus of Asteraceae does Liabum oblanceolatum belong? : Vegetative characters have the answer - Gutiérrez, Diego Germán (2006)
The West Indian species Liabum oblanceolatum Urb. & Ekman was established on the basis of sterile young specimens represented by acaulescent herbs with rosulate leaves. However, these specimens have important traits that do not correspond to Liabum Adans. More than 90 genera of Asteraceae occur in Hispaniola (= Santo Domingo), but only 14 of them include species represented by acaulescent herbs with rosulate or grouped leaves at the base of the stem. From these genera, Chaptalia Vent. and Liabum are the most similar to the types of L. oblanceolatum. Habit, leaf arrangement, lamina shape, leaf margin, leaf surface, leaf margin intrasection, leaf venation, leaf pubescence, leaf trichomes, stomata and upper surface leaf cuticle were analysed in the type specimens of L. oblanceolatum and in species of Chaptalia and Liabum of Hispaniola. The vegetative trichomes are described in detail. The analysis reveals that the type specimens of L. oblanceolatum fit with all the vegetative traits of Chaptalia angustata Urb.